Bodies of knowledge: embodied rhetorics in theory and practice - Knoblauch, A. Abby, editor; Moeller, Marie E., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Challenges the homogenizing (mis)understandings of knowledge construction and provides a complex discussion of what happens when we do not attend to embodied rhetorical theories. Language is always a reflection of culture, to attempt to erase language and knowledge that reflect minoritized and historically excluded cultural experiences obscures the legitimacy of such experiences both within and outside the academy.--Provided by publisher.
The body's turn in rhetorical studies / William P. Banks -- Introduction: bodies, embodiments, and embodied rhetorics / A. Abby Knoblauch and Marie E. Moeller -- Violence and beneficence in the rhetorics of touch / Scot Barnett -- Disrupting embodied silence / Katherine Bridgman -- Towards an olfactory rhetoric: scent, affect, material, embodiment / Sara DiCaglio -- Embodying history: the bodies and affects of museum rhetorics / Julie D. Nelson -- The role of intra-body resonance in political organizing / Nadya Pittendrigh -- Discomfort training in the archives: embodied rhetoric in feminist advocacy / Margaret Brooker, Julie Myatt, and Kate Pantelides -- Fannie Barrier Williams's Citizen-Woman: embodying rhetoric at the 1893 World's Columbian Exposition / Kristie S. Fleckenstein -- Re-writing maternal bodies on the Senate floor / Ruth Osorio -- Criminals and victims: the embodied rhetorics of unaccompanied Latinx children as represented in Spanish- and English-language media / Megan Strom -- The successful text is not always the one that murders me to protect you / Vyshali Manivannan -- Hooking-up embodied technologies, queer rhetorics, and Grindr's grid / Caleb Pendygraft -- Avowed embodiment: self-identification, performative strategic attire, and TRAP karaoke / Temptaous Mckoy -- Matters that (em)body / Kellie Sharp-Hoskins and Anthony Stagliano.
Keywords: Human body and language; Language and culture; Rhetoric -- Study and teaching -- Social aspects; Academic writing -- Social aspects